Armed struggle in Italy: the limits to criminology in the analysis of political violence - Ruggiero, Vincenzo (The British journal of criminology, 2010)
Repeated calls to criminologists to engage in the analysis of violent political conflict have been followed by an abundant production of literature within the discipline. This article examines such production and attempts to delineate the limits to criminology in the analysis of political violence. By presenting interview extracts from a case study centred on violent political conflict in Italy during the 1970s and 1980s, I demonstrate why criminology should seek supplementary explanatory categories within the broader realm of social theory, rather than rely exclusively on the theories and assumptions of traditional criminology